2008
DOI: 10.1270/jsbbs.58.437
|View full text |Cite
|
Sign up to set email alerts
|

Major QTLs for eating quality of an elite Japanese rice cultivar, Koshihikari, on the short arm of chromosome 3

Abstract: To identify the chromosomal regions controlling the eating quality of Koshihikari rice, we performed a quantitative trait locus (QTL) analysis using two backcross inbred lines (BILs): N-BILs (79 lines derived from a cross of Nipponbare/Koshihikari//Nipponbare) and K-BILs (89 lines derived from a cross of Nipponbare/ Koshihikari//Koshihikari). We evaluated several components of the eating quality of cooked rice, namely glossiness, taste, stickiness, hardness, and overall evaluation, based on sensory tests by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 30 publications
3
47
0
1
Order By: Relevance
“…Several studies have identified QTLs for such physicochemical properties and also for the eating quality of cooked rice using indica/japonica cross populations (Bao et al, 2000;Li et al, 2003;Ogata et al, 1996;Otsuki et al, 1997;Takeuchi et al, 2007;Wan et al, 2004). However, few studies have identified QTLs related to eating quality in the same manner in japonica/japonica cross populations (Kobayashi and Tomita, 2008;Takeuchi et al, 2007Takeuchi et al, , 2008Tanaka et al, 2006;Wada et al, 2006;2008). In this study, we identified 21 QTLs in seven regions on chromosomes 1, 4, 6, 7, 8 and 11 for seven traits (Table 3, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified QTLs for such physicochemical properties and also for the eating quality of cooked rice using indica/japonica cross populations (Bao et al, 2000;Li et al, 2003;Ogata et al, 1996;Otsuki et al, 1997;Takeuchi et al, 2007;Wan et al, 2004). However, few studies have identified QTLs related to eating quality in the same manner in japonica/japonica cross populations (Kobayashi and Tomita, 2008;Takeuchi et al, 2007Takeuchi et al, , 2008Tanaka et al, 2006;Wada et al, 2006;2008). In this study, we identified 21 QTLs in seven regions on chromosomes 1, 4, 6, 7, 8 and 11 for seven traits (Table 3, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Five stable QTLs and 21 additional QTLs associated with eating quality were previously identified using chromosome segment substitution lines (CSSLs) derived from a cross of Asominori (japonica) and IR24 (indica), and by using backcross inbred lines (BILs) derived from a cross of Koshihikari/Kasalath (indica)//Koshihikari and CSSLs, respectively (Ebitani et al, 2005;Wan et al, 2004). A few studies have also identified QTLs for eating quality in doubled haploid (DH)lines or RILs derived from crosses between different japonica strains (Kobayashi and Tomita, 2008;Suh et al, 2006;Takeuchi et al, 2008;Tanaka et al, 2006;Wada et al, 2008). DNA markers closely linked to these QTLs have made it possible to more efficiently develop rice cultivars with a higher eating quality (Lestari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These analyses have identified several unique QTLs for heading date (Matsubara et al 2008), culm length (Hori et al 2009), pre-harvest sprouting resistance (Hori et al 2010), and eating quality (Takeuchi et al 2008;Kobayashi and Tomita 2008;Wada et al 2008). The success of this approach implies that the use of a wide range of cross combinations might increase the opportunity to detect unique QTLs.…”
Section: Comparison With Qtl Clusters Identified In Other Studiesmentioning
confidence: 99%
“…Takeuchi et al (2007) detected common QTLs on Chr 3 and Chr 6 using backcross inbred lines (BILs) and chromosome segment substitution lines (CSSLs) derived from crosses between 'Koshihikari' and indica cultivar 'Kasalath'. Takeuchi et al (2008) also detected QTLs on Chr 3 (two regions) and Chr 6 using two kinds of BILs (K-BILs; derived from a cross Nipponbare/Koshihikari// Koshihikari, and N-BILs; Nipponbare/Koshihikari// Nipponbare), and showed QTLs on Chr 3 were commonly detected regions, whose nearest marker was RM4108. identified QTLs for stickiness on Chr 1, 3, 6, 7, and 8 using recombinant inbred lines (RILs) derived from a cross, between Sakihikari, which is genetically closely related to 'Koshihikari', and Nipponbare.…”
mentioning
confidence: 87%
“…Quantitative trait locus (QTL) analysis has been performed to identify the chromosome regions controlling eating quality (Tanaka et al, 2006;Takeuchi et al, 2007Takeuchi et al, , 2008; Wada et al, 2008). Although QTLs for stickiness of cooked rice were detected on chromosome (Chr) 2 (Tanaka et al, 2006;, many reports suggest that the short arm of Chr 3 has the highest effect on the eating quality of cooked rice.…”
mentioning
confidence: 99%